Effects of Internal Exposure of Radioactive 56MnO2 Particles on the Lung in C57BL Mice - Zhaslan Abishev; Bakhyt Ruslanova; Saulesh Apbassova; Nailya Chaizhunussova; Dariya Shabdarbayeva; Almas Azimkhanov; Kassym Zhumadilov; Valeriy Stepanenko; Sergey Ivanov; Peter Shegay; Masaharu Hoshi; Nariaki Fujimoto (Current Issues in Molecular Biology, 2023)
The investigation of the radiation effects of the atomic bombing in Hiroshima and Nagasaki has revealed concerns about the impact of the residual radioactive dust produced in the soil. Manganese-56 is one of the major radioisotopes produced by neutrons from the bomb; hence, we previously examined the biological effects of manganese dioxide-56 (56MnO2) in Wistar rats, in which significant changes were found in the lung. In the present study, ten-week-old male C57BL mice were exposed to three doses of radioactive 56MnO2, stable MnO2 particles, or external γ-rays (2 Gy) to further examine the effects of 56MnO2 in a different species. The estimated absorbed radiation doses from 56MnO2 were 26, 96, and 250 mGy in the lung. The animals were examined at 3, 14, and 70 days post exposure. Histologically, no exposure-related changes were found in the lungs of any group. However, pulmonary mRNA expression of aquaporin 1, which is a useful marker for lung pathophysiology, was significantly elevated at 14 and 70 days, although no such changes were found in the mice exposed to external γ-rays (2 Gy). These data indicated that the inhalation exposure to 56MnO2 particles, with <250 mGy of organ doses, produced significant biological responses in the lung.